The demographic and clinical characteristics of leprosy in Saudi Arabia. Issue 5 (September 2016) - Alotaibi, Mohammad H.; Bahammam, Salman A.; ur Rahman, Saeed; Bahnassy, Ahmed A.; Hassan, Imad S.; Alothman, Adel F.; Alkayal, Abdulkareem M.
Summary: Leprosy is a chronic disease caused by Mycobacterium leprae. Although the occurrence of leprosy has declined in Saudi Arabia, it has not yet been eradicated. To our knowledge, this descriptive retrospective study is the first to assess the clinical presentation of leprosy at the time of diagnosis in Saudi Arabia. All study subjects were leprosy patients admitted to Ibn Sina hospital, the only referral hospital for leprosy in Saudi Arabia, between January 2000 and May 2012. A total of 164 subjects, the majority of whom (65%) were between 21 and 50 years of age, were included, and the male-to-female ratio was 2.8:1. Of these 164 patients, 63% were Saudis, and 77% of all admitted patients were from the western region. Lepromatous leprosy was observed most frequently (33%), and 31% of cases had a positive history of close contact with leprosy. At the time of diagnosis, 84% of all subjects presented with skin manifestation. The prevalence of neurological deficit at the time of diagnosis was 87%. Erythema nodosum leprosum (E.N.L.) developed in only 10% of all subjects. Further studies are needed to determine the clinical characteristics pertaining to each type of leprosy in the region, and training courses in caring for and diagnosing patients with leprosy should be organized for health workers.